Phenotype of mice with inducible ablation of GluA1 AMPA receptors during late adolescence: Relevance for mental disorders. Issue 4 (23rd December 2013) - Inta, Dragos; Vogt, Miriam A.; Elkin, Hasan; Weber, Tillmann; Lima‐Ojeda, Juan M.; Schneider, Miriam; Luoni, Alessia; Riva, Marco A.; Gertz, Karen; Hellmann‐Regen, Julian; Kronenberg, Golo; Meyer‐Lindenberg, Andreas; et al.
ABSTRACT Adolescence is characterized by important molecular and anatomical changes with relevance for the maturation of brain circuitry and cognitive function. This time period is of critical importance in the emergence of several neuropsychiatric disorders accompanied by cognitive impairment, such as affective disorders and schizophrenia. The molecular mechanisms underlying these changes at neuronal level during this specific developmental stage remains however poorly understood. GluA1‐containing AMPA receptors, which are located predominantly on hippocampal neurons, are the primary molecular determinants of synaptic plasticity. We investigated here the consequences of the inducible deletion of GluA1 AMPA receptors in glutamatergic neurons during late adolescence. We generated mutant mice with a tamoxifen‐inducible deletion of GluA1 under the control of the CamKII promoter for temporally and spatially restricted gene manipulation. GluA1 ablation during late adolescence induced cognitive impairments, but also marked hyperlocomotion and sensorimotor gating deficits. Unlike the global genetic deletion of GluA1, inducible GluA1 ablation during late adolescence resulted in normal sociability. Deletion of GluA1 induced redistribution of GluA2 subunits, suggesting AMPA receptor trafficking deficits. Mutant animals showed increased hippocampal NMDA receptor expression and no change in striatal dopamine concentration. Our data provide new insight into the role of deficient AMPA receptors specifically during late adolescence in inducing several cognitive and behavioral alterations with possible relevance for neuropsychiatric disorders. © 2013 Wiley Periodicals, Inc.